PARADIGMA PENDIDIKAN ISLAM: TINJAUAN EPISTEMOLOGI - Usman Abu Bakar (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The article elaborates the paradigm of Islamic education from epistemological perspective. In fact, the development of technology, information and free trade has been as problems in the globalization era. The condition appears anxiety toward the existence of Indonesian education in preparing competitive human resources. Indonesian Education is still trapped by dichotomy between religious science and secular one. In the globalization era, however, the dichotomy is not popular anymore and the separation is one of some factors that makes Indonesia left behind other countries. The emergence of the Acts No. 20 of 2003 concerning National Educational System is truly an attempt of Indonesian country to reach equality among countries in the world. Thus, the Islamic concept of non-dichotomy education finds its significance. In terms of Islamic contexts, it is necessary to reformulate the paradigm of science that underlines all educational system in order to fulfill the demand of society and era.